Treatment of lentigo maligna of the head and neck with staged excision in South Africa : assessing surgical excision margins with Melan A, SOX10 and PRAME immunohistochemistry - De Wet, Johann (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMed)--Stellenbosch University, 2022.